Design Strategy of Ion Conductive Polymers - NISHIMURA, Naomi; OHNO, Hiroyuki (KOBUNSHI RONBUNSHU, 2011)
Ion conductive materials are indispensable for the design of many devices. For smaller and/or lighter weight devices, it is necessary to transform ion conductive materials from the liquid-state to the solid-state. Polymers are important materials to support this strategy. There is an increasing number of studies on ion conductive polymers started with poly(ethylene oxide) in the 1970s. The initial studies are mainly on simple mixtures of polar polymers and salts, but soon the focus was turned to gels to improve the mechanical properties. However, addition of low-molecular-weight solvents to these gels did not solve their poor mechanical properties. Then, micro-phase separation of the mixture of polymers and liquid components has been studied to solve these drawbacks. In the present review, these three subjects are explained with recently published results, and future aspects are also mentioned.